Determining greenwashing in global ESG research: A bibliometric analysis of themes, trends, and regional focus - Arieftiara, Dianwicaksih; Marzuki, Marziana Madah (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study aims to explore global research trends on greenwashing in the context of ESG practices using a bibliometric approach. By examining co-occurrence of keywords and the geographical origin of publications, this research identifies how greenwashing is conceptualized and studied across regions. The analysis uses data from the Scopus database, comprising 1,642 documents across all years, and utilizes VOSviewer to map keyword relations and country distributions. The findings reveal that frequently occurring terms are closely related to corporate ethics, transparency, and sustainability claims, indicating the growing academic concern around deceptive environmental practices. The results also show that most research originates from developed economies such as the United States, China, the United Kingdom, and Germany, reflecting the influence of strict regulatory frameworks and advanced ESG standards. However, emerging countries like India, Malaysia, and Indonesia are also gaining visibility in the field, suggesting an increasing awareness of environmental accountability. Furthermore, the uneven global distribution of studies highlights a lack of harmonized approaches in identifying greenwashing, especially in regions with less regulatory oversight. This study contributes by (1) integrating fragmented theoretical perspectives into a coherent analytical framework, (2) identifying regional and institutional research disparities, and (3) proposing a structured future research agenda and policy implications for ESG regulation and sustainability assurance. The study is limited to Scopus-indexed publications and does not assess empirical firm-level outcomes. Practical implications highlight the need for harmonized ESG standards, mandatory assurance, and the use of digital technologies to mitigate greenwashing.